Composition and Cornel West : Notes toward a Deep Democracy - Gilyard, Keith, 1952- (Book collections on Project MUSE., 2008)
Composition and Cornel West: Notes toward a Deep Democracy identifies and explains key aspects of the work of Cornel West-the highly regarded scholar of religion, philosophy, and African American studies-as they relate to composition studies, focusing especially on three rhetorical strategies that West suggests we use in our questioning lives as scholars, teachers, students, and citizens. In this study, author Keith Gilyard examines the strategies of Socratic Commitment (a relentless examination of received wisdom), Prophetic Witness (an abiding concern with justice.